An overview of Hospital‐at‐home versus other models of care - Hai Liang Marc Wong; Chong Yau Ong; Hui Juan Ngo; Si Sen Yeo; Mui Hua Jean Lee (Journal of General and Family Medicine)
Abstract Despite being increasingly adopted in various regions, the model of Hospital‐at‐home can still appear to be confusing to many healthcare workers. The authors examined and summarized the existing concepts and implementations of Hospital‐at‐home. How Hospital‐at‐home contrasts to traditional inpatient models were outlined.